INFLUENCE OF COMPLEX MICRO-ALLOYING ON PHYSICO-MECHANICAL CHARACTERISTICS OF MEDIUM-CARBON STEEL 40G2L - V. V. Volik; L. K. Chebotarj; V. V. Lunev (Литьë и металлургия)
The influence of complex micro alloying on physical and mechanical characteristics of medium-carbon steel 40G2L is shown.